Disease-related differences in resting-state networks: a comparison between localized provoked vulvodynia, irritable bowel syndrome, and healthy control subjects. Issue 5 (May 2015) - Gupta, Arpana; Rapkin, Andrea J.; Gill, Zafar; Kilpatrick, Lisa; Fling, Connor; Stains, Jean; Masghati, Salome; Tillisch, Kirsten; Mayer, Emeran A.; Labus, Jennifer S.
Abstract : Abstract: Localized provoked vulvodynia (LPVD) affects approximately 16% of the female population, but biological mechanisms underlying symptoms remain unknown. Like in other often comorbid chronic pain disorders, altered sensory processing and modulation of pain, including central sensitization, dysregulation of endogenous pain modulatory systems, and attentional enhancement of pain perception, have been implicated. The aim of this study was to test whether regions of interest showing differences in LPVD compared to healthy control subjects (HCs) in structural and evoked-pain neuroimaging studies, also show alterations during rest when compared with HCs and a chronic pain control group (irritable bowel syndrome [IBS]). Functional magnetic resonance imaging was performed during resting state in 87 age-matched premenopausal females (29 LPVD, 29 HCs, and 29 IBS). Group-independent component analysis and general linear models were applied to investigate group differences in the intrinsic connectivity of regions comprising sensorimotor, salience, and default mode resting-state networks. Subjects with LPVD showed substantial alterations in the intrinsic connectivity of these networks compared with HCs and IBS. The intrinsic connectivity of many of the regions showing group differences during rest were moderately associated with clinical symptom reports in LPVD. Findings were robust to controlling for affect and medication usage. The current findings indicate that subjects with LPVD have alterations in the intrinsic connectivity of regions comprising the sensorimotor, salience, and default mode networks. Although shared brain mechanisms between different chronic pain disorders have been postulated, the current findings suggest that some alterations in functional connectivity may show disease specificity. Abstract : Differences in the resting-state connectivity of brain regions within the sensorimotor, salience, and default mode networks are demonstrated in localized provoked vulvodynia.